Evaluation of the Prevalence of Maxillary Sinuses Abnormalities through Spiral Computed Tomography (CT) - Drumond, João Paulo Nunes; Allegro, Bruna Bianca; Novo, Neil Ferreira; de Miranda, Sérgio Luís; Sendyk, Wilson Roberto (International Archives of Otorhinolaryngology, 2017)
Introduction Maxillary sinus disease is common and numerous disorders can affect this anatomical area. Abnormalities can be classified as: non-neoplastic, neoplastic benign, and neoplastic malignant.Objective Evaluate through CT the prevalence of diseases in maxillary sinuses, using the Radiology Department's database of a hospital in São Paulo city. Methods The sample consisted of 762 facial CT scans that we divided into three groups: Group A (12–19 years old); Group B (20–49 years old); Group C (above 50 years old); and male or female. We considered the following pathological processes: I - Mucoperiosteal Thickening; II - Chronic Sinusitis; III - Chronic Odontogenic Sinusitis; IV - Rhinosinusitis; V - Polypoid Lesions; VI - Bone Lesions; VII - Neoplasms; VIII - Antrolith; IX - Foreign Bodies; X - Oroantral Fistula.Results Our study found that 305 exams (40.02%) were normal and 457 exams (59.97%) were abnormal. We found the following disease frequencies: focal mucoperiosteal thickening (21.25%); polypoid lesions (10.76%); chronic sinusitis (7.48%); chronic odontogenic sinusitis (2.29%); neoplasms (2.03%); rhinosinusitis (1.77%); bone lesions, foreign bodies and oroantral fistula in 0.65%; 0.13% and 0.06% respectively. There was no significant difference between male and female, and Groups A, B, or C when relating the frequencies of abnormalities found. There was no significant difference between male and female and the age group for the side of the altered maxillary sinus.Conclusion We observed a high prevalence of sinus maxillary diseases. Mucoperiosteal thickening; acute, chronic, and odontogenic sinusitis; polypoid lesions and neoplasms have high prevalence in maxillary sinuses. Thus, facial CT exam was effective for the evaluation of diseases in maxillary sinuses.
Keywords: maxillary sinus; spiral computed tomography; diagnostic imaging; otolaryngology; epidemiology